2013
DOI: 10.1007/s00220-013-1683-4
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Free Unique Continuation Estimates and Applications to Random Schrödinger Operators

Abstract: We prove a unique continuation principle or uncertainty relation valid for Schrödinger operator eigenfunctions, or more generally solutions of a Schrödinger inequality, on cubes of side L ∈ 2N + 1. It establishes an equi-distribution property of the eigenfunction over the box: the total L 2 -mass in the box of side L is estimated from above by a constant times the sum of the L 2 -masses on small balls of a fixed radius δ > 0 evenly distributed throughout the box. The dependence of the constant on the various p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 27 publications
3
94
0
Order By: Relevance
“…Our main theorem unifies and generalizes all the results mentioned so far and makes the dependence on the model parameters explicit. Indeed, our scale-free unique continuation principle answers positively a question asked in [40]. A partial answer was given already in [27].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our main theorem unifies and generalizes all the results mentioned so far and makes the dependence on the model parameters explicit. Indeed, our scale-free unique continuation principle answers positively a question asked in [40]. A partial answer was given already in [27].…”
Section: Introductionmentioning
confidence: 59%
“…A partial answer was given already in [27]. While [40] concerns the case of a single eigenfunctions, [27] treats linear combinations of eigenfunctions corresponding to very close eigenvalues. For a broader discussion we refer to the summer school notes [43].…”
Section: Introductionmentioning
confidence: 99%
“…This allowed the dropping of the ln term in (3). A full answer to the question raised in [17] was given by the following Theorem.…”
Section: Fig 1 Examples Of S δ (5) For Different δ-Equidistributed mentioning
confidence: 99%
“…More than this, there are several quantitative formulations of unique continuation which proved to be useful in a variety of applications, see e.g. [BK05,RL12,BK13,RMV13,NTTV16]. For instance, Bourgain and Kenig [BK05] showed that if ∆u = V u in R d , u(0) = 1 and u, V ∈ L ∞ (R d ) then for all x ∈ R d with |x| > 1 we have max |y−x|≤1 |u(y)| > c · exp −c ′ (log|x|)|x| 4/3 .…”
Section: Introductionmentioning
confidence: 99%
“…For the application to random Schrödinger operators it is crucial that the result is scale-free, i.e. C is independent of L. In [RMV13] the question was raised whether a similar estimate holds for finite linear combinations of…”
Section: Introductionmentioning
confidence: 99%